EbolaTracks: an automated SMS system for monitoring persons potentially exposed to Ebola virus disease - Tracey, L.; Regan, Annette; Armstrong, P.; Dowse, G.; Effler, P. (European Centre for Disease Prevention and Control, 2015)
We report development and implementation of a short message service (SMS)-based system to facilitate active monitoring of persons potentially exposed to Ebola virus disease (EVD), whether returning from EVD-affected countries, or contacts of local cases, should they occur. The system solicits information on symptoms and temperature twice daily. We demonstrated proof-of-concept; however this system would likely be even more useful where there are many local contacts to confirmed EVD cases or travellers from EVD-affected countries.